Climate Adaptability of Medicinal Plants in the Thar Desert: A Review of Morphological and Physiological Strategies - Panwar, Suman (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Thar Desert, one of the most arid and ecologically challenging landscapes in the Indian subcontinent, hosts a remarkable diversity of medicinal plants that have withstood extreme temperatures, low precipitation, and nutrient-poor soils. These plants not only contribute to local healthcare traditions but also demonstrate extraordinary survival strategies that make them vital subjects of ecological and pharmacological interest. This review paper synthesizes existing literature on the various morphological and physiological adaptations that enable medicinal plant species to survive and thrive in the harsh climatic conditions of the Thar Desert. Key morphological traits such as deep and extensive root systems, thick cuticles, reduced or modified leaf structures (including spines and trichomes), and compact plant architecture are examined for their role in minimizing water loss and maximizing resource uptake. The review also explores physiological mechanisms, particularly the role of Crassulacean Acid Metabolism (CAM) and C4 photosynthesis, which enhance water-use efficiency and contribute to drought resistance. By consolidating findings from ecological, botanical, and ethnobotanical studies, this paper highlights the resilience and ecological importance of these plant species. It also underscores the need for their conservation in the face of climate change and increasing anthropogenic pressures. This synthesis aims to support further research in arid zone plant ecology and inform strategies for sustainable utilization and preservation of medicinal plant resources in desert ecosystems.